Protection against Violence in the Work Environment in the Light of ILO Convention No. 190 - Nowak, Monika (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The article concerns ILO Convention No. 190 on the elimination of violence and harassment in the world of work. The author analyzes the subjective and objective scope of the Convention, including the concept of violence and harassment at work adopted therein, as well as the obligation to take action in the field of prevention and legal protection of people affected by violence in the work environment. The article also explains the ILO Convention’s obligation to adopt an “inclusive, integrated and gender-responsive approach” to prevent violence at work and protect the worker from its consequences.